Improving Community Knowledge on Health Insurance Utilization through Health Education - Sianipar, Imelda Martina G; Ardayani, Tri; Tresnadjaja, Reynaldi; Sinaga, Anni; Sujana, Treesia; Hariningsih, Wintari (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2024)
The purpose of this activity is to plan community service activities to solve the problems obtained based on the priority situation analysis of the problems obtained by providing health education to the community to always maintain health. The method used consists of preparation, implementation, and closing. The implementation was carried out through counseling which took place at the RW 11 Mosque, Jayagiri Desara Village, Lembang District, West Bandung Regency, which was attended by 36 participants. From the survey results, it was also known that before the counseling, 57% of respondents realized that they had the potential to get high-risk diseases, but only half of them had health insurance to fund the risk of their disease. After the counseling, it was again identified that 64% of respondents have the potential for high-risk diseases, and now all respondents realize the need for health financing. This community service activity is expected to provide real benefits to the Jayagiri Village community and become an inspiration for similar efforts in various regions.